2011
DOI: 10.1038/jp.2011.151
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric parameters and Doppler findings in cerebral circulation as predictors of 1 year neurodevelopmental outcome in asphyxiated infants

Abstract: Objective: To establish the association of cardiotocography (CTG) and other obstetric parameters with pulsed Doppler findings in cerebral arteries during the first day of life, and to compare the cerebral artery Doppler with other determinants of asphyxia in predicting 1-year neurological outcome in asphyxiated full-term infants.Study Design: Cerebral blood flow velocity (CBFV) were measured from the anterior cerebral (ACA) and basilar (BA) arteries in 30 asphyxiated and 30 healthy-term infants using pulsed Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Julkunen also found that increased CBF by Doppler was a better predictor of adverse neurological outcomes at 1 year of age in asphyxiated infants as compared with other markers. 40 Elevated CBF in HC males may either directly contribute to lower scores in males or indirectly serve as a marker of fetal brain inflammation. Although correlations did exist between blood flow parameters and BSID scores for long-term outcomes, these data are speculative and not as strong as the primary outcome of sex-specific CBF data.…”
Section: Discussionmentioning
confidence: 99%
“…Julkunen also found that increased CBF by Doppler was a better predictor of adverse neurological outcomes at 1 year of age in asphyxiated infants as compared with other markers. 40 Elevated CBF in HC males may either directly contribute to lower scores in males or indirectly serve as a marker of fetal brain inflammation. Although correlations did exist between blood flow parameters and BSID scores for long-term outcomes, these data are speculative and not as strong as the primary outcome of sex-specific CBF data.…”
Section: Discussionmentioning
confidence: 99%
“…High cerebral blood flow velocity has been demonstrated as a sensitive predictor of neonatal mortality and poor neurological outcome at 12 mo of age (29,30); thus, the cerebral circulatory consequences of open ETT suction may result in brain injury. ETT suctioning is most frequently performed during the first 72 h after delivery, with a single infant undergoing as many as six suction procedures during this period (19).…”
Section: Chorioamnionitis Alters Hemodynamicsmentioning
confidence: 99%
“…These findings support earlier reports that TCD could be used as a diagnostic and prognostic modality for infants with severe HIE [31] and can be used to guide medical therapy and management of cerebral hypoperfusion, which is associated with higher morbidity and mortality rates [31] . Moreover, Julkunen et al [32] found that TCD diagnosis of HIE Grade 2-3 and estimation of ACA-blood flow velocity can predict the outcome in asphyxiated infants better than cardiotocography, acid basement status, Apgar scores, or asphyxia markers. Thereafter, Lovett et al [33] documented favorable neurologic outcomes of patients who had TCD-detected near normal flow velocity with intermittently intact cerebral autoregulation.…”
Section: Discussionmentioning
confidence: 99%